Peningkatan Hasil Belajar Peserta Didik dalam Pembelajaran Pendidikan Pancasila Menggunakan Model Game Based Learning (GBL) di Kelas IV UPT SD Negeri 16 Padang Magek Kabupaten Tanah Datar (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to improve the learning outcomes of students in learning Pancasila Education using a game-based learning model. This type of research is Classroom Action Research (PTK) with qualitative and quantitative approaches. The research is carried out in two cycles, each cycle involves four stages, namely planning, implementation, observation and reflection stages. The subject of the study is class IV students totaling 27 students. Data collection was carried out through tests, observations, and interviews. The results of the study showed that the increase was evidenced by the results in the aspect of the teaching module in the first cycle with an average of 83.33% (B) and increased in the second cycle with an average of 91.67% (A). In the aspect of teacher activity in the first cycle with an average of 82.82% (B) and increased in the second cycle with an average of 93.75% (A). In the aspect of student activity in the first cycle with an average of 81.25% (B) and increased in the second cycle with an average of 90.63% (A). As well as in the learning outcomes of students in the first cycle with an average of 78.4 (C) and increased in the second cycle with an average of 90.43 (A). Based on this data, it can be concluded that using the game-based learning model can improve the learning outcomes of grade IV students of SDN 16 Padang Magek, Tanah Datar Regency.